Methamphetamine use is associated with childhood sexual abuse and HIV sexual risk behaviors among patrons of alcohol-serving venues in Cape Town, South Africa - Meade, Christina S. (2012)
BACKGROUND: South Africa’s Western Cape has experienced a dramatic increase in methamphetamine (“meth”) use over the past decade. There is concern that meth may further fuel the HIV epidemic in this country because of its association with risky sexual behaviors. This study describes the prevalence of meth use and its relation to HIV sexual risk behaviors among patrons of alcohol-serving venues. METHODS: Participants (N=3,328) were surveyed in 12 venues in a mixed race township. Logistic regression models were used to examine the relations between meth use and sexual risk behaviors, and structural equation models were used to test whether meth use mediates the relationship between childhood sexual abuse and current sexual risk. RESULTS: Meth use in the past 4 months was more common among Coloured than Black persons (10.5% vs. 3.5%). Meth users were more likely than non users to use marijuana, inhalants, and injection drugs, have a history of childhood sexual and/or physical abuse, and experience and/or perpetrate intimate partner violence. Among both men and women, meth use was associated with greater odds of engaging in sexual risk behaviors, and meth use partially mediated the relationships between childhood sexual abuse and all sexual risk behaviors. CONCLUSIONS: Meth users in this setting are at increased risk for HIV due to their greater likelihood of engaging in sexual risk behaviors and being in violent relationships. There is an urgent need to provide targeted HIV prevention and substance abuse treatment to meth users living in townships in Cape Town.